Manajemen Pendidikan Islam berbasis Moderasi Beragama: Model Penguatan Karakter dan Harmoni Sosial di Sekolah - Khairiah Khairiah; Sapura Sapura; Mahyiddin Mahyiddin; M. Fadli (Program Pascasarjana UNU Surakarta, 2026)
Islamic education is expected to develop students' character and promote social harmony. However, globalization, digitalization, and the rise of intolerance have created a gap between these ideals and educational practice. This study aims to analyze Islamic education management based on religious moderation as a model for strengthening character and fostering social harmony in schools. The novelty of this research lies in integrating Islamic education management functions with the principles of religious moderation as a comprehensive framework for character development. This study employed a qualitative approach using library research. Data were collected from books, scientific journals, and relevant documents and analyzed through data reduction, data presentation, and conclusion drawing. Based on the synthesis, this study proposes the Islamic Education Management Based on Religious Moderation (MPI-MB) Model, which integrates the Planning, Organizing, Actuating, and Controlling (POAC) management functions with the four indicators of religious moderation promoted by the Indonesian Ministry of Religious Affairs: national commitment, tolerance, anti-violence, and accommodation of local culture. The model is further strengthened through religious digital literacy to address the challenges of digital hidden curriculum and social media algorithms in the digital era. This conceptual synthesis extends previous studies by positioning religious moderation not merely as instructional content but as a comprehensive educational governance framework that supports inclusive, adaptive, and sustainable Islamic education management.